Sassy : Little Sister is not my name - Draper, Sharon M. (Sharon Mills) (Draper, Sharon M. (Sharon Mills). Sassy., 2009)
Fashion-savy Sassy does not like being the smallest student in her fourth-grade class, until a family emergency calls for a pint-sized hero.